Exploring self-victimhood’s place in moral personality and unethical organizational behavior - Thomas Wilmore; Ana Kriletic; Daniel Svyantek; Lilah Donnelly (International Journal of Personality Psychology)
Recent research has shown that a tendency for interpersonal victimhood (TIV) predicts maladaptive thinking and antagonistic behavior. However, understanding TIV’s place in the nomological network of personality variables used to predict moral behavior in organizations.  This paper attempted to bridge this gap by examining TIV’s associations with morally relevant personality traits and TIV’s prediction of unethical organizational behavior in two studies. For the studies, we relied on two samples of U.S. adults recruited via an online crowdsourcing platform (NTotal = 1,080) using survey methods. Study 1 (N = 485) showed that TIV had a sizeable loading onto an overarching Dark Factor of Personality (D), which contained TIV, the Dark Tetrad, and moral disengagement. Study 2 (N = 405-595) showed that TIV predicted counterproductive work behavior (CWB) and unethical pro-organizational behavior (UPB), even after controlling for morally relevant HEXACO traits and demographic variables. Supplemental analyses indicated that TIV’s rumination facet primarily drives its relationship with CWB, while its lack of empathy facet primarily drives its relationship with UPB. TIV tended to have small to moderate positive correlations with dark traits (e.g., the Dark Triad, moral disengagement) (r = 0.30-0.50) and small negative correlations with light traits (e.g., the Light Triad, Honesty-humility, moral identity-internalization). This research provides evidence supporting TIV’s place in the nomological network of moral personality and its influence on destructive organizational behavior.